Integrasi Sanksi Administrasi dan Sanksi Pidana dalam Kejahatan Pertambangan Batu Bara (Studi Putusan Pengadilan No. 123/Pid.Sus/2024/PN.Smr) - Rina Susanti; Akhmaddhian, Suwari (Universitas Kuningan, 2025)
This study aims to analyze the administrative and criminal law provisions in coal mining crimes and their application in Decision Number 123/Pid.Sus/2024/PN Smr. The research method used is normative juridical, with a statutory, conceptual, and court decision study approach, utilizing primary and secondary legal materials. The results indicate that administrative mining law comprehensively regulates licensing, supervision, and administrative sanctions mechanisms as instruments for initial control of mining activities. On the other hand, criminal law serves as a means of enforcement against serious violations. However, in its application, the analyzed decisions demonstrate a tendency toward criminal-centric law enforcement, without optimizing administrative law instruments. The conclusion is that coal mining law enforcement does not yet reflect proportional integration between administrative and criminal law. Therefore, a strengthened, hierarchical, integrated law enforcement approach oriented toward improving mining governance is needed. The government, particularly the Ministry of Energy and Mineral Resources, the National Police, and the Supreme Court, need to strengthen the monitoring and enforcement mechanisms for administrative and criminal sanctions consistently against coal mining violations.